A cross-sectional analysis of Trichomonas vaginalis infection among heterosexual HIV-1 serodiscordant African couples. (4th April 2017) - Bochner, Aaron F; Baeten, Jared M; Rustagi, Alison S; Nakku-Joloba, Edith; Lingappa, Jairam R; Mugo, Nelly R; Bukusi, Elizabeth A; Kapiga, Saidi; Delany-Moretlwe, Sinead; Celum, Connie; Barnabas, Ruanne V
Abstract : Objectives: Trichomonas vaginalis is the most prevalent curable STI worldwide and has been associated with adverse health outcomes and increased HIV-1 transmission risk. We conducted a cross-sectional analysis among couples to assess how characteristics of both individuals in sexual partnerships are associated with the prevalence of male and female T. vaginalis infection. Methods: African HIV-1 serodiscordant heterosexual couples were concurrently tested for trichomoniasis at enrolment into two clinical trials. T. vaginalis testing was by nucleic acid amplification or culture methods. Using Poisson regression with robust standard errors, we identified characteristics associated with trichomoniasis. Results: Among 7531 couples tested for trichomoniasis, 981 (13%) couples contained at least one infected partner. The prevalence was 11% (n=857) among women and 4% (n=319) among men, and most infected individuals did not experience signs or symptoms of T. vaginalis . Exploring concordance of T. vaginalis status within sexual partnerships, we observed that 61% (195/319) of T. vaginalis -positive men and 23% (195/857) of T. vaginalis -positive women had a concurrently infected partner. In multivariable analysis, having a T. vaginalis -positive partner was the strongest predictor of infection for women (relative risk (RR) 4.70, 95% CI 4.10 to 5.38) and men (RR 10.09, 95% CI 7.92 to 12.85). For women, having outside sex partners, gonorrhoea, and intermediate or high Nugent scores for bacterial vaginosis were associated with increased risk of trichomoniasis, whereas age 45 years and above, being married, having children and injectable contraceptive use were associated with reduced trichomoniasis risk. Additionally, women whose male partners were circumcised, had more education or earned income had lower risk of trichomoniasis. Conclusions: We found that within African HIV-1 serodiscordant heterosexual couples, the prevalence of trichomoniasis was high among partners of T. vaginalis -infected individuals, suggesting that partner services could play an important role identifying additional cases and preventing reinfection. Our results also suggest that male circumcision may reduce the risk of male-to-female T. vaginalis transmission.